The Concept of the Dignity of the Human Person According to Thomas Aquinas - Roeske, Maria (Filozofia Chrześcijańska, 2025)
For Thomas and his contemporaries, personal dignity is the basis of being a person, a formal element that constitutes a person. According to Aquinas, the dignity of a person is its especially perfect way of existence consisting in existing by itself and for itself, that is, in existing as an end in itself. Being an end in itself is realized through freedom. It is visible above all in the fact that a person realizes his/her own, self-determined goals and is not just a tool for realizing the goals of other people or God. Thomas’s concept is surprisingly coherent with the paradigm of dignity adopted in contemporary international law and the constitutional orders of many countries. It justifi es why a person cannot be treated as an object. Therefore it may provide solid anthropological foundations for modern-day legal orders and for ethics. It also explains the trinitarian and christological dogmas, allowing to avoid the heresies of tritheism and Nestorianism.